Evaluation of Income and Postharvest Losses of Yam in Southern Agricultural Zone of Nasarawa State - Daniel Akaakohol Iorzua; Agnes Agbanugo Ikwuba; James Timbee Aan; Solomon Chimela Nwafor (Archives of Current Research International, 2020)
The study evaluated the income and postharvest losses of yam in Nasarawa State Nigeria from 2014 to 2018. The study employed the use of cross sectional design. The study was conducted in Nasarawa state, Nigeria between October 2019 and June 2020. Data for the study were collected using multistage sampling technique from a sample of three hundred and eighty seven (387) respondents. The result showed that majority of the respondents (322) 83%, were male, and within the age range of 31-40 years 158(41%) followed by the age bracket of 41-50: 97(25%); 323(84%) of the respondents were married with average household size of 8.0 persons per household while 87% of the respondents have had one form of formal education or the other. The spearman correlation matrix showing the relationship between the income and post-harvest losses of the farmers further revealed that there is a significant relationship between income and postharvest losses of yam farmers in the studied area. Coefficient of determination (R square) value was 0.922 with a P value of 0.00. The result reveals a significant and strong positive correlation betweenthe income and post-harvest losses of the farmers. The study thus concluded that most of the respondents were high income earners but suffer post-harvest losses throughout yam production chain in various measures. The extent of losses differs from farmer to farmer but does not differ in the communities sampled in the study area.